2010
DOI: 10.1158/0008-5472.sabcs10-pd05-11
|View full text |Cite
|
Sign up to set email alerts
|

Abstract PD05-11: Development, Characterization, and Effective In Vitro Treatment of an Endoxifen Resistant Breast Cancer Cell Line

Abstract: Background: A major issue surrounding the use of therapeutic drugs for the treatment of breast cancer is the eventual development of resistance. Endoxifen, the most potent tamoxifen metabolite, is being developed as a novel endocrine therapy for the treatment of endocrine responsive breast cancer patients. While numerous studies have investigated the process of tamoxifen resistance, no such data exist regarding the mechanism by which cells develop resistance to endoxifen. Here, we describe the development and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…However, treatment effectiveness is limited by high rates of de novo and acquired resistance during treatment [8]. E, an active metabolite of TMX, can also fail because of acquired resistance [6,7]. Hence, the aim of the present study was to determine the efficacy of CM administered for the prevention of decreased sensitivity of BC cells to E by coadministration with β-E2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, treatment effectiveness is limited by high rates of de novo and acquired resistance during treatment [8]. E, an active metabolite of TMX, can also fail because of acquired resistance [6,7]. Hence, the aim of the present study was to determine the efficacy of CM administered for the prevention of decreased sensitivity of BC cells to E by coadministration with β-E2.…”
Section: Discussionmentioning
confidence: 99%
“…E exerts its anticancer effects by degrading ER alpha, which leads to the inhibition of estrogen-induced BC cell proliferation [4]. However, BC cell resistance to endocrine treatment, including E, is likely to develop overtime [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Currently, endoxifen is being developed as a novel drug for the treatment of endocrine responsive breast cancer patients. 3 Hawse et al 2 showed that endoxifen had similar actions to selective estrogen receptor antagonist (fulvestrant) with regard to its ability to degrade ERα through proteasome degradation system, to block ERα-mediated transcriptional activation and to prevent estrogeninduced breast cancer cell proliferation. 2 A study was conducted by Wu et al 1 and showed that cells treated with high endoxifen (E) concentrations, i.e.…”
mentioning
confidence: 99%